Diversity of midgut microbiota in ticks collected from white-tailed deer (Odocoileus virginianus) from northern Mexico - Molina Garza, Zinnia Judith; Cuesy León, Mariana; Baylón Pacheco, Lidia; Rosales Encina, José Luis; Galaviz Silva, Lucio (The Korean Society for Parasitology and Tropical Medicine, 2024)
Ticks host different pathogens as endosymbiont and nonpathogenic microorganisms and play an important role in reproductive fitness and nutrient provision. However, the bacterial microbiomes of white-tailed deer ticks have received minimal attention. This study aimed to examine the bacterial microbiome of ticks collected from Odocoileus virginianus on the Mexico–United States border to assess differences in microbiome diversity in ticks of different species, sexes, and localities. Five different tick species were collected: Rhipicephalus microplus, Dermacentor nitens, Otobius megnini, Amblyomma cajennense, and A. maculatum. The tick microbiomes were analyzed using next-generation sequencing. Among all tick species, the most predominant phylum was Proteobacteria, followed by Actinobacteria and Firmicutes. The ticks from Tamaulipas and Nuevo León presented the highest bacterial species diversity. Acinetobacter johnsonii and A. lwoffii were the common bacterial species in the microbiome of all ticks, Coxiella were present in R. microplus, and Dermacentor nitens also exhibited a Francisella-like endosymbiont. The microbiome of most females in D. nitens was less diverse than that of males, whereas R. microplus occurs in females, suggesting that microbiome diversity is influenced by sex. In the bacterial communities of A. maculatum and O. megnini, Candidatus Midichloria massiliensis, and Candidatus Endoecteinascidia fumentensis were the most predominant endosymbionts. These results constitute the initial report on these bacteria, and this is also the first study to characterize the microbiome of O. megnini.